Construction and characterization of peroxisome proliferator-activated receptor-gamma co-activator 1 alpha (PGC-1α over-expressing cell line derived from human hepatocyte carcinoma HepG2 cells) - Novotna, Aneta; Doricakova, Aneta; Pavek, Petr; Dvorak, Zdenek (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2013)
AIMS: The aim was develop stable human cell line stable over-expressing transcription co-activator peroxisome proliferator-activated receptor gamma co-activator 1α (PGC-1α) with restored hepatospecific functions and increased expression of major xenobiotic metabolizing enzymes. METHODS: Six clones of HepG2-PGC-1α and one control clone HepG2-pcDNA3 were isolated and analyzed for secretion of hepatospecific markers, fibrinogen, albumin and alpha1-antitrypsin. Expression levels of protein and mRNA of hepatocyte nuclear factor (HNF4α), pregnane X receptor (PXR) and aryl hydrocarbon receptor (AhR) were determined. We measured basal and ligand inducible expression of CYP1A1 and CYP3A4. RESULTS: Stably transfected cell line HepG2-PGC-1α derived from HepG2 cells over-expressing PGC-1α displayed increased secretion of fibrinogen, but not albumin or alpha1-antitrypsin compared to parent HepG2 cells. We found increased levels of HNF4α, PXR and AhR proteins but not their mRNAs in HepG2-PGC1 cells. Basal expression of CYP3A4 protein in HepG2-PGC-1α cells was increased but rifampicin-inducible expression of CYP3A4 protein was lowered in comparison with parent HepG2 cells. Induction of CYP3A4 mRNA varied between 1.3 - 1.9 fold in individual clones. Expression of TCDD-inducible CYP1A1 protein was lower in HepG2-PGC-1α cells than in parent HepG2 cells. Induction of CYP1A1 mRNA by TCDD in HepG2-PGC-1α cells was comparable with that in parent HepG2 cells and ranged between 103 - 198 fold. CONCLUSION: Stable expression of PGC-1α in HepG2 cells restores several hepatospecific functions, such as secretion of fibrinogen, expression of HNF4α1 and xenoreceptors PXR and AhR. However, the expression and induction of key drug-metabolizing enzymes (CYP1A1 and CYP3A4) were not improved.
Keywords: fibrinogen; PPAR gama; Biomarkers, Tumor; Cytochrome P-450 CYP1A1; lidé; nádorové biomarkery; PPARGC1A; hepatocyty; pregnanový X receptor; buňky Hep G2; polychlorované dibenzodioxiny; Cytochrome P-450 CYP3A; Pregnane X Receptor; transfekce; Hep G2 Cells; Transcription Factors; cytochrom P-450 CYP1A1; Basic Helix-Loop-Helix Transcription Factors; Teratogens; Humans; Hepatocytes; Fibrinogen; teratogeny; receptory aromatických uhlovodíků; transkripční faktory bHLH; Hepatocyte Nuclear Factor 4; transkripční faktory; Receptors, Aryl Hydrocarbon; cytochrom P-450 CYP3A; Gentamicins; Peroxisome Proliferator-Activated Receptor Gamma Coactivator 1-alpha; steroidní receptory; Receptors, Steroid; hepatocytární jaderný faktor 4; gentamiciny; Polychlorinated Dibenzodioxins; Transfection; PPAR gamma